Cervical Cancer Screening in Pregnancy and Postpartum: A North Indian Hospital Based Prospective Observational Study - Gill, Poonam; Gaurav, Amrita; Khoiwal, Kavita; Kumari, Om; Bahadur, Anupama; Agarwal, Aanchal; Chowdhuri, Sandipan; Chaturvedi, Jaya (Asian Pacific Journal of Cancer Biology, 2020)
Introduction: In India, cervical cancer stands as the 2nd most common female cancer and it is the 2nd most leading cause of deaths in women aged 15 to 44 years. The first visit to the gynecologist for most of the women in India is during pregnancy, thereby making it a fair opportunity for the screening of premalignant and malignant cervical disease. Methods: A prospective observational study was conducted in the Department of Obstetrics and Gynaecology, AIIMS, Rishikesh, Uttarakhand, India from January 2018 to January 2019. The Pap smear testing of 237 spontaneously conceived antenatal women, aging between 20 to 35 years was performed. The same women were followed up for postnatal testing after 6 weeks of delivery. Results: Out of 237, 8 women were reported positive for pre malignant lesions of cervix in the antenatal testing, 5 cases of ASCUS, 1 case of AGC, 1 case of ASC-H & 1 case of HSIL. In the postnatal Pap smear testing, 37 women were lost to follow-up including 1 case of ASCUS. Postnatal Pap smear testing of the remaining 200 women showed that 193 women who were reported NILM in the antenatal period remained unchanged in the postnatal screening too. Out of the 7 women who tested positive, 4 cases of ASCUS, 1 case of AGC and 1 case of ASC-H showed regression, giving result as NILM in the postnatal screening test. Out of the 7 positive antenatal tests, 1 case which was reported as HSIL in the antenatal screening, remained unchanged in the postnatal period. Conclusion: The study concluded that there is significant regression (p<0.01) of Positive Pap smear findings from antenatal to postnatal period. Hence, it is imperative to repeat Pap smear test in postnatal period.